A survey of the prevalence and burden of pain and symptoms amongst HIV positive patients attending HIV treatment clinics in the University of the Witwatersrand Academic Hospital clinics - Farrant, Lindsay Georgina (Department of Public Health and Family Medicine, 2014)
This study was designed to measure the symptom prevalence and symptom burden amongst patients attending three HIV treatment clinics in greater Johannesburg, and to assess the relationship of these to CD4 count, viral load, WHO stage, functional status and HAART. Patients at the three clinics were invited, using convenience sampling, to participate in completing the interviewer administered Memorial Symptom Assessment Scale-Short Form (MSAS-SF) which assesses the 7 day prevalence and distress for 28 physical symptoms and prevalence and frequency of four psychological symptoms. Demographic and clinical data, including initial and latest CD4 counts, initial and latest viral loads and information on HAART use, were collected from the participants and from their clinic files.